Conditioned sounds enhance visual processing. - Fabrizio Leo (Public Library of Science (PLoS), 2014)
This psychophysics study investigated whether prior auditory conditioning influences how a sound interacts with visual perception. In the conditioning phase, subjects were presented with three pure tones ( =  conditioned stimuli, CS) that were paired with positive, negative or neutral unconditioned stimuli. As unconditioned reinforcers we employed pictures (highly pleasant, unpleasant and neutral) or monetary outcomes (+50 euro cents, -50 cents, 0 cents). In the subsequent visual selective attention paradigm, subjects were presented with near-threshold Gabors displayed in their left or right hemifield. Critically, the Gabors were presented in synchrony with one of the conditioned sounds. Subjects discriminated whether the Gabors were presented in their left or right hemifields. Participants determined the location more accurately when the Gabors were presented in synchrony with positive relative to neutral sounds irrespective of reinforcer type. Thus, previously rewarded relative to neutral sounds increased the bottom-up salience of the visual Gabors. Our results are the first demonstration that prior auditory conditioning is a potent mechanism to modulate the effect of sounds on visual perception.